Performance of Conventional and Islamic Banks (Global Journal of Management and Business Research, 2016)
This paper investigates the differences in mean cost, revenue, and profit efficiency of conventional and Islamic banks based on size and location by using three sets of samples over the 1992-2007period from 54 countries. The study uses financial ratio analysis. The results showed that Islamic banks in both samples are more cost efficient than the conventional banks. While, the results of revenue efficiency (ROAE) ratio reveal that conventional banks are more profitable. However, the results of profit efficiency were inclusive.
Keywords: cost; revenue; and profit efficiency of conventional and Islamic banks